2022
DOI: 10.3390/microorganisms10030662
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling of Antibiotic-Resistant Escherichia coli Isolates from Surface Water of Agricultural Drainage in North-Western Mexico: Detection of the International High-Risk Lineages ST410 and ST617

Abstract: Aquatic environments are recognized as one of the main reservoirs for the emergence and dissemination of high-risk lineages of multidrug-resistant (MDR) bacteria of public health concern. However, the genomic characteristics of antibiotic-resistant Escherichia coli isolates from aquatic origins remain limited. Herein, we examined the antibiotic resistance and virulence genomic profiles of three E. coli recovered from surface water in northwest Mexico. Antimicrobial susceptibility testing, whole-genome sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
0
3
0
1
Order By: Relevance
“…Despite some environemtal isolates possibly losing some adhesion properties in vitro infection models, they still possess virulence properties according to our cytotoxicity assays. ST410 is a high-risk MDR clone of E. coli commonly associated with carbapenemase genes that carry blaOXA-181 and blaNDM-5 and with cross-sectorial Mexico's agricultural drainage(60). The ST410 isolates described in this study were not MDR, but carried the CS23 operon in combination with LT and STh.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…Despite some environemtal isolates possibly losing some adhesion properties in vitro infection models, they still possess virulence properties according to our cytotoxicity assays. ST410 is a high-risk MDR clone of E. coli commonly associated with carbapenemase genes that carry blaOXA-181 and blaNDM-5 and with cross-sectorial Mexico's agricultural drainage(60). The ST410 isolates described in this study were not MDR, but carried the CS23 operon in combination with LT and STh.…”
mentioning
confidence: 77%
“…ST410 was previously reported in soil samples from the Choqueyapu River and carried the bla OXA-1 gene (11). Studies have also found that E. coli ST410 is associated with vegetables on the municipal market in Ecuador (59) or surface water from Mexico’s agricultural drainage (60). The ST410 isolates described in this study were not MDR, but carried the CS23 operon in combination with LT and STh.…”
Section: Discussionmentioning
confidence: 99%
“…), Asia (South Korea, 32 Singapore, 33 India, 34 China, 35 etc. ), Africa, 36 North America (United States, 37 Mexico, 38 etc.) and South America (Brazil, 39 Chile 40 et al), etc.…”
Section: Discussionmentioning
confidence: 99%
“…DNA extraction and sequencing was performed as previously described [22] . A single E. coli colony was grown in Luria-Bertani (LB) broth overnight at 37 ± 2 °C under aerobic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…A quality control assessment, filtering, and further assembly of raw sequencing data were performed as previously reported [22] . The FastQC program, version 0.11.9 ( https://www.bioinformatics.babraham.ac.uk/projects/fastqc/ ), and Cutadapt, version 2.4 [23] , were employed to evaluate and process the raw genomic reads, respectively.…”
Section: Methodsmentioning
confidence: 99%